Neurosurgery as a Career Choice among Recent Medical Graduates from the Institute of Medicine, Nepal: A Cross-sectional Study - Parajuli, Subigya; Gyawali, Purnima; Subedi, Prarthana; Bhatta, Om Prakash; Mukhia, Rupesh; Sedain, Gopal; Sharma, Mohan Raj (Nepal Journal of Neuroscience, 2022)
Introduction: The career choice of a medical graduate is often a complex process with multiple factors playing a part. Neurosurgery in Nepal is gradually growing and there is a huge interest in the academia to draw more graduates into neurosurgery. There is a paucity of data regarding the career choice of medical graduates from Nepal. The aim of this study was to determine the potential barriers and facilitators for choosing a future career as a neurosurgeon. Methods: A descriptive cross-sectional study was carried out on all recent medical graduates in the last two weeks of their internship in 2021 from three medical colleges in Kathmandu. Variables included demographic characteristics, preferred specialty, willingness to choose neurosurgery and reasons for it, and the reasons for not choosing neurosurgery if done so. Frequency and percentages were used to describe the categorical variables. Mean and median were used to describe continuous variables. A comparison between two categorical variables (factors for choosing Neurosurgery as a career and factors that encouraged not to choose Neurosurgery) was made. Results: Twenty-one out of 87 respondents preferred neurosurgery as their future career. The common motivating factors for choosing neurosurgery were innate interest in neurosurgery, motivation from seniors and mentors during clinical clerkship, and the glamour of the specialty. The main barriers were the perceived generally poor outcome of the neurosurgical patients, long hours of surgery, innate disinterestedness, long training and not having enough opportunities to get accredited training in the country. Conclusion: Around Twenty-four percentage of graduates preferred neurosurgery as a future career. When the barriers are addressed there will probably be more medical graduates inclined to join Neurosurgery which will help in solving the shortage of neurosurgical manpower in Nepal.